Studi Identifikasi dan Prevalensi Endoparasit pada Saluran Pencernaan Ikan Kerapu Tikus (Cromileptes altivelis) di Keramba Jaring Apung Unit Pengelola Budidaya Laut Situbondo, Jawa Timur [Prevalence Study And Identification Of Endoparasites On Humpback Grouper Gastrointestinal (Cromileptes altivelis) In Floating Net Cage Marine Culture Management Unit Situbondo, East Java] - Kismiyati Kismiyati; Rahayu Kusdarwati; Mohammad Faizal Ulkhaq (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract Humpback grouper (Cromileptes altivelis) or also known as polkadot grouper is one of the excellent fish commodities in Indonesia which has trading value reached $ 90-150/kg. As a consumed fish, humpback grouper are needed for beverage at luxuries restaurant and hotel in the world. As major export commodities in Indonesia, since the 1990's the techniques of grouper cultivation in float net rats are enhanced to fulfill international market demand. Humpback grouper fish cultivation techniques in float net cages cannot be separated from the problems in any cultivate activities, one of the causes is a disease and one of the diseases that rushed humpback grouper is parasite. The disadvantages that caused by the parasite is fish' weight loss. The purpose of this study is to determine the types of endoparasites that attacked the digestive system of humpback grouper (Cromileptes altivelis) in float net cages and also to discuss the prevalences of endoparasites that attack the digestive of humpback grouper (Cromileptes altivelis) in float net cages. The method of this research is descriptive. The sampling was done in once for 60 fishes with the length range of fish is around 15-20 cm and 4 months old from the float net. The number of each fishes samples that were taken 5-10% from the total of population, where the number of humpback grouper populations in each raft float net are 200 fishes. The main parameters that observed in this study were endoparasites identification species that attack the digestive system of humpback grouper (Cromileptes altivelis) in float net cages and the prevalence rates for each endoparasites. The supporting parameters in this study were the water quality in float net cages which includes temperature, pH and salinity are measured during the sample taken. The results showed that 60 samples taken from four float nets 6 fishes were positive infected endoparasitic of trematodes and nematodes, besides 4 fishes are positive infected worms Echinostoma which belong to the class of Trematodes and 2 fishes infected worms Camallanus carangis that belongs to the class Nematoda. The prevalence values for each of the worm are 6.67% for Echinostoma and 3.33% for Camallanus carangis. The research concern the identification and prevalence of endoparasites in Humpback grouper at hatchery is needed to early finding out the attack of endoparasites and to break the flow of endoparasitic spreading.